Advances in computational intelligence : 17th Mexican International Conference on Artificial Intelligence, MICAI 2018, Guadalajara, Mexico, October 22-27, 2018, Proceedings.: 17th Mexican International Conference on Artificial Intelligence, MICAI 2018, Guadalajara, Mexico, October 22-27, 2018, Proceedings. Part I (2018) - Unknown
No abstract available